Genetic evidence of differential dispersal pattern in the Asiatic wild dog: Comparing two populations with different pack sizes - Modi, Shrushti; Mondol, Samrat; Ghaskadbi, Pallavi; Nigam, Parag; Habib, Bilal (Frontiers in Ecology and Evolution, 2022)
Dispersal is a multi-causal, crucial life-history event in shaping the genetic and behavioral structure of mammals. We assessed the dispersal pattern of dholes aka Asiatic wild dog (Cuon alpinus), a social monogamous mammal at two tiger reserves of Maharashtra with different degrees of pack size and competition with tigers i.e. Tadoba-Andhari (TATR, smaller pack size, higher tiger density) and Nawegaon-Nagzira (NNTR, larger pack size, lower tiger density). We used the microsatellite data of 174 individual genotypes (98 males and 67 females) to assess the dispersal pattern of dholes from two populations with varying pack size, tiger density, and landscape connectivity using gene flow as a proxy. We compared the population structure, pairwise F statistics, assignment index, and relatedness across a spatial scale. Overall, the results suggested a difference in sex-bias dispersal pattern for the two sub-populations, exhibiting significant results for female-biased dispersal in the TATR population with a smaller pack size and higher tiger density. Our study highlights the variability in sex-biased dispersal patterns in two different populations which could be the consequence of different variables such as pack size, tiger density, and geographical scale. The study warrants further quantitative investigation including several factors such as individual behavior, pack composition, pack size, tiger density, etc. In the present Anthropocene era, determining the sex bias in dispersal patterns for a short-range, pack-living carnivore will help in devising an effective conservation management plan for their long-term survival.